LECTURER’S PERCEPTION ON THE IMPLEMENTATION OF PROBLEM-BASED LEARNING (PBL) APPROACH IN TEACHING AND LEARNING - Nurazwa Ahmad; Noor Aslinda Abu Seman; Mohamad Ali Selimin; Juliana Abdul Halip; Nurul Karimah Wan Ahmad (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Problem-based learning (PBL) was known as the student-centered pedagogy where it involves the student to experience solving complex real-world problems and the teacher acts as a facilitator in crafting trigger materials to promote the learning concepts. This study aims to investigate and identify the level of usefulness and challenges as well as the level of student achievement through the perception of academic staff’ on the implementation of PBL in classrooms in Malaysia. A quantitative study was conducted, and the data was collected through a survey questionnaire on 98 lecturers all over Malaysia. The findings from the analysis indicate that lectures in Malaysia have a high perception of PBL implementation in the classroom. Overall, the findings enhance the understanding of higher institution lecturers’ perception of PBL in terms of the usefulness of PBL as one dynamic and active approach that transforms dramatically the routine lecture-based learning. Findings also suggest that sufficient training to learners is required in implementing PBL effectively, thus indirectly facilitate the focus of students that lead to the achievement of course learning outcomes.